Pemberdayaan Karang Taruna melalui Peningkatan Keterampilan Teknologi Berbasis Internet of Things (IoT) di Kelurahan Gamer Kota Pekalongan - Ari Putra Wibowo; Widiyono (PT. Karya Inovatif Nusantara, 2026)
The development of Internet of Things (IoT) technology has created opportunities for communities to utilize digital technology in solving everyday problems. However, most members of the Karang Taruna youth organization in Gamer Village, Pekalongan City, had limited knowledge and skills related to IoT technology. This community service program aimed to improve participants’ understanding and practical skills in electronics, programming, computer networking, and IoT implementation. The program was conducted from July 22 to July 27, 2025, at the Gamer Village Hall, involving 25 participants. The implementation methods included lectures, demonstrations, hands-on practice, and project-based mentoring. The results showed a significant increase in participants’ knowledge, indicated by the improvement of average pretest scores from 56.31 to 79.61 in the posttest, representing a 41.38% increase. Furthermore, participants successfully developed four IoT projects, including temperature and humidity monitoring systems, automatic irrigation systems, gas leakage detection devices, and flood detection systems. The program effectively improved technological literacy and practical IoT skills among youth participants.